تسجيل ثلاثة أنواع جديدة من الطحالب البحرية الخضراء (Bryopsidales, Chlorophyta) على الشاطئ السوري - عباس, آصف (Latakia University Journal -Biological Sciences Series, 2016)
تمّ جمع 3 أنواع من الطحالب الخضراء ذات الأصل الهادي-الهندي من شاطئ اللاذقية أثناء شهر نيسان لعام 2013 و للمرة الأولى: Codium arabicum: المشرة خضراء داكنة، مسطحة و مفصصة، ذات مظهر إسفنجي، الجيوب المنتفخة ذات قمة مدورة و سميكة. Codium taylorii: المشرة قائمة خضراء داكنة، الفروع عريضة ومسطحة عند نقطة التفرع، الجيوب المنتفخة تنتهي بقمة مدورة قليلاُ. Codium parvulum: المشرة خضراء فاتحة، متفرعة بشكل غير منتظم في الأجزاء السفلية، الفروع النهائية ثنائية اسطوانية، الجيوب المنتفخة ذات قمة مدورة أو منبسطة قليلاُ. دُرس الشكل المورفولوجي والتشريحي والتوزع الجغرافي لهذه الأنواع الجديدة و أضيفت الى الفلورا السورية. Three green algal Indo-Pacific species were collected from the coast of Lattakia during April 2013 for the first time: Codium arabicum: Thallus dark green,procumbent, lobed, sponge form, utricles with rounded tips and thick. Codium taylorii: Thallus erect , dark green, branches completely compressed at the dichotomies, utricles with apices slightly rounded. Codium parvulum: Thallus light green, irregularly branched in lower portion, ultimate branches dichotomous, cylindrical, utricles apices rounded or slightly flattened. Data concerning morphology, anatomy and geographical distribution of the species are presented. Three new records of genus codium has been added to the flora of Syria.